Long-Term Success in the Management of an Extensive Medial Canthal Basal-Cell Carcinoma with Vismodegib - Argyrios Tzamalis; Georgios Lavasidis; Ioannis Tsinopoulos; Nikolaos Ziakas (Journal of Current Ophthalmology)
Purpose: To present a case of an extensive basal-cell carcinoma (BCC) of the medial canthus that was successfully treated with vismodegib. The introduction of vismodegib and other Hedgehog pathway inhibitors into clinical practice has provided a new option for the nonsurgical management of periocular BCC. Methods: An 85-year-old male was referred to our clinic with a pigmented nodular BCC but declined any medical intervention. Two years later, the patient returned with an extensive periocular lesion. Through biopsy and magnetic resonance imaging, we confirmed the diagnosis of a nodular-ulcerative BCC extending into the medial orbit. Surgery and radiotherapy were declined. Therefore, oral treatment with vismodegib was initiated. Results: After 3 months, complete tumor regression was noted, and the medication was discontinued. The patient remained tumor-free till the last follow-up, 3 years posttreatment. No treatment-related side effects were observed. Conclusion: This case demonstrates the clinical value of vismodegib in advanced periocular BCC, particularly when surgery is inappropriate or declined by the patient.